ROLE OF E-DICTIONARY IN CLASSROOM TEACHING - Jose. S, Franklin Thambi; Preethi, J.; Hartono, Rudi (International Journal of Psychosocial Rehabilitation, 2020)
Electronic dictionary is a dictionary of digital form which can be used to access any number of words or lexemes. It can also be said as the dictionary in the digital form. At present, there are different types of dictionaries which can be downloaded in the smartphones or tablets as apps. And these apps can be used in the classrooms during teaching hours. Classroom is a room where usually teaching and learning takes place. Classrooms are set up in all kinds of educational institutions such as training institutes, schools, colleges and universities. Usually classrooms are closed rooms to avoid outside distractions which interrupt the teaching or learning processes. In the technological era, classrooms have white board or LED screens, markers, e-books, teaching pads, etc. It is also equipped with all the facilities like fan, air condition, chair, table, writing pads, micro phone, speaker, etc. Classroom consists of lecture and discussion. The lecture can include text based teaching, images, audio visual, slides, etc. in the classroom. Discussion is the process of talking about some subject matter usually in order to reach a decision or to exchange thoughts. Students can be given opportunity to discuss on a particular topic which is very much related to that day’s lecture or lesson. During the lecture and discussion, the teachers and students have to use dictionary for unrelated words, new words, technical words, etc. For this purpose, electronic dictionary termed as e-dictionary can be used in the classroom. This article tries to trace out the role of electronic dictionaries in classroom teaching.